Avaliação de métodos de determinação do potencial pozolânico de resíduos da indústria de cerâmica vermelha - Sebastiany, Lucas Deivid (Universidade do Vale do Rio dos Sinos, 2014)
Along the last few decades the civil construction industry has been using many residues from the metallurgical and energetic industries. More recently, it has been looking for different ways of incorporating other residues originated by the primary sector (as ashes from sugar cane and rice husk), the ceramic sector (white and red ceramic) and the construction industry itself (construction and demolition wastes). Considering the strong ceramics sector in the State of Rio Grande do Sul, this project aims to investigate the pozzolanic potential of red clays after calcination in different temperatures (700ºC, 900ºC and 1000ºC), comparing them to a commercial reference, the metakaolin. There were used two methods, proposed by NBR 5751/2012 and NBR 5752/2012, two others modified methods based on these testing procedures, but adopting a fixed water/cement ratio and the Luxàn method. The Ca(OH)2 consumption was determined by thermogravimetry (TG) and by the derivate of TG (DTG). The characteristics of the ceramic pozzolans were determined after crushing, using X-ray fluorescence, EDS, X-ray diffraction, measurement of specific surface area (BET), laser granulometry particle size analyse and loss due to fire. The metakaolin samples had the higher pozzolanic activity. The ceramics calcinated at 700ºC had the best results on the ceramics samples. There are a high co-relation between the thermogravimetric analysis, the Luxàn method and the NBR5752/2012 modified method, but there is no correlation with the methods proposed by NBR 5751/2012 and NBR 5752/2012.
Evaluation of methods for determining the pozzolanic potential of red ceramic waste
Keywords: Argilas calcinadas; Resíduo de cerâmica vermelha; Métodos para determinação do potencial pozolânico; Calcinated clays; Red ceramic waste; Methods to determine the pozzolanic potential; ACCNPQ::Engenharias::Engenharia Civil